Synthesis and application of derivatizable oligonucleotides. - Gibson, K J (1987)
To investigate protein-DNA interactions, we have synthesized a versatile phthalimide-protected 5-(3-aminopropyl)-2'-deoxyuridine nucleoside probe. The modified residue was incorporated into deoxyoligonucleotides by automated synthesis. The standard oligonucleotide workup also exposed the pendent amino group, which was found to react with either fluorescent labelling agents or, as detailed below, a photoactivatable cross-linking agent. In the dark, a strand with a photolabile group adjacent to the 3' end served as a primer for synthetic template-directed DNA synthesis by the Klenow fragment of E. coli DNA polymerase I, by bacteriophage T4 DNA polymerase, and by avian myeloblastosis virus (AMV) reverse transcriptase. Brief illumination with 302 nm light afforded covalent complexes between DNA and the polymerases; labelling of AMV reverse transcriptase was predominantly in the beta subunit.